Língua inglesa aliada à cultura e às novas tecnologias em uma escola pública: um estudo de caso - Corrêa Júnior, Plínio (2020)
Language and culture are deeply linked. Culture is in habits, way of life, customs, among other areas having been created by men at the same time that it coordinates them. Language is also linked to culture and it is an important part of communication and understanding between men. Thus, in learning a foreign language it is important to know the culture of the target language so that learning is effective. This dissertation addresses some categories related to the definition of what culture is, with a focus on teaching English language, and the importance they play in the educational area. The culture that permeates the areas of human knowledge, the culture created by man and that guides him will be addressed in this research together with the cultural repertoire of the students because both culture and cultural repertoire are connected here. Therefore, this research aims to get to know and thus be able to deal better with these students, subjects of rights who need greater and better attention so that they can help them in the construction of their knowledge. The focus of this research will be an analysis of the method used in English language classes at a public school in the 3rd year of high school in the city of São Paulo through a cultural bias. Regarding the category referring to the analysis of culture, Zygmunt Bauman's studies on culture will serve as a foundation. From the perspective of Paulo Freire, they will also analyze some of the student's perspectives in their cultural repertoire, their life experiences, their particularities, their knowledge of the world. These items must be taken into account, through the Freire's look in dialogue with the concepts of Bauman proposed here. This research also brings some reflections about some aspects of the culture of the English language in the teaching-learning relationship and, in addition, addresses some questions related to how to implement a teaching method with the culture in the teaching of the English language and if it is necessary in the learning, in addition to showing the importance of this language, especially in a globalized world, where a lot of information and knowledge is acquired through access to the English language. So the purpose of this research is to verify if culture is properly taken into account in language teaching, how it is seen and treated in public schools in English language classes, how this is evident and if it is really evident in the context of the third year high school in a public school, and the student is about to finish the last year. In addition, this research will address the dialogues that can be established between education, culture and new technologies and how they can be combined in favor of an effective learning of the English language with the use of new technologies such as internet, games and cell phones in the classroom. This whole scenario carried out through a cultural bias. So, through a cultural bias, these are questions that will guide our reflective path, before reaching the intervention proposal presented in the last segment of the dissertation, in which we will present the teaching of the English language considered from cultural issues with access made possible by the use of new technologies, such as internet and cell phones.